Ferritic stainless steel for copper phosphorus brazing and water heater using same

A tailored ferritic stainless steel composition with controlled Cu and other elements addresses the inferior brazing properties of ferritic stainless steels, achieving enhanced brazing performance for water heaters by suppressing oxide film formation and ensuring a strong metallic bond with phosphor copper.

JP7600970B2Active Publication Date: 2024-12-17JFE STEEL CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021196470
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-12-02
Publication Date
2024-12-17
Estimated Expiration
2041-12-02

AI Technical Summary

Technical Problem

Ferritic stainless steels exhibit inferior brazing properties when used with phosphor copper brazing materials, particularly at temperatures between 600 to 950°C, limiting their application in water heaters.

Method used

A specific composition of ferritic stainless steel is developed, including controlled amounts of Cu, Si, Mn, Cr, and other elements to suppress the formation of oxide films, enhancing brazing properties by ensuring a metallic bond with the phosphor copper brazing material.

Benefits of technology

The new composition achieves a spread rate of the phosphor copper brazing material exceeding 150%, improving the brazing performance and suitability for water heater applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600970000001
    Figure 0007600970000001
Patent Text Reader

Abstract

To provide a ferritic stainless steel for phosphor-copper brazing that exhibits good brazing property when brazing is performed using a phosphor-copper brazing material.SOLUTION: Provided is a ferritic stainless steel for phosphor-copper brazing that has a composition containing, in mass%, C: 0.003 to 0.020%, Si: 0.01 to 0.60%, Mn: 0.01 to 0.40%, P: 0.040% or less, S: 0.020% or less, Cr: 16.0 to 27.0%, Ni: 0.01 to 2.50%, Al: 0.010% or less, Cu: 0.40 to 0.80%, Nb: 0.10 to 0.50%, N: 0.020% or less, and the balance being Fe and unavoidable impurities.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a ferritic stainless steel for copper phosphorus brazing and a water heater using the same, and more particularly to a ferritic stainless steel that exhibits good brazeability when brazing is performed using a copper phosphorus brazing material. [Background technology]

[0002] Copper is used in large quantities in the field of water heaters, including gas water heaters and electric water heaters. For example, copper pipes are widely used as the piping for carrying the water and heat transfer medium used in these devices. In addition, from the perspective of protecting the global environment, environmentally friendly water heaters, which have become increasingly popular in recent years, are equipped with heat exchangers, which also use copper.

[0003] In recent years, the demand for copper for electric wires and conductors has increased due to the growing demand for power infrastructure in emerging countries and the shift to electric vehicles, resulting in a tight supply-demand situation for copper. Demand for copper is expected to continue to increase, and reducing copper usage in response to rising copper prices has become an important issue.

[0004] Against this background, the water heater industry is moving away from copper to other materials, particularly ferritic stainless steel, which is relatively inexpensive and has excellent corrosion resistance.

[0005] The piping and heat exchanger parts of water heaters are mainly made of components that are bonded and assembled by phosphorus copper brazing using a Cu-containing brazing material, particularly a phosphorus copper brazing material with an appropriate brazing temperature of 600 to 950° C. For this reason, the materials used for these components are required to have good brazeability in phosphorus copper brazing (hereinafter also simply referred to as brazeability).

[0006] In general, the brazeability of ferritic stainless steel is inferior to that of copper (Cu), and therefore improvement is required.

[0007] For example, Patent Document 1 describes a stainless steel with excellent brazability, characterized in that it contains, by mass%, C: 0.001 to 0.1%, Si: over 1.5 to 4.0%, Mn: 0.05 to 4.0%, Cr: 10.5 to 30%, Ni: 35% or less, N: 0.001 to 0.4%, and further contains one or both of Ti: 0.002 to 0.030% and Al: 0.002 to 0.10%, with the balance being Fe and unavoidable impurities, the contents of Si, Ti and Al satisfying (Formula 1), and an oxide film having a composition that satisfies (Formula 2) is formed on the surface. S m / (Ti m +Al m )≧40 (Formula 1) 1.2×Si m / Fe m ≦Si f / Fe f ≦5×Si m / Fe m ... (Formula 2) In (Formula 1) and (Formula 2), the element name with the subscript f represents the content of each element in the oxide film in atomic %, and the element name with the subscript m represents the content of each element in the base steel in mass %."

[0008] Patent Document 2 describes a ferritic stainless steel having excellent Cu brazeability, which has a composition, by mass%, containing C: 0.01 to 0.03%, Si: 1.00% or less, Mn: 1.50% or less, P: 0.04% or less, S: 0.03% or less, Ni: 0.6% or less, Cr: 17 to 25%, Mo: 2.50% or less, Cu: 0.10 to 0.50%, N: 0.030% or less, Nb: 7×(C+N)% or more, 0.80% or less, Al: 0.022% or less, with the balance being Fe and unavoidable impurities, and which satisfies the following formula (1): C+6Si-4Al-72Ti≧1.5 ··· (1) formula Here, C, Si, Al, and Ti in formula (1) represent the mass percentage of each element." [Prior art documents] [Patent documents]

[0009] [Patent Document 1] International Publication No. 2016 / 152854 [Patent Document 2] JP 2018-145497 A Summary of the Invention [Problem to be solved by the invention]

[0010] The ferritic stainless steel described in Patent Document 1 contains a certain amount of Si, and ensures brazeability by forming an oxide film where Si is concentrated. The ferritic stainless steel described in Patent Document 2 contains a certain amount of Nb, and ensures brazeability by utilizing the carbides formed in the steel.

[0011] There was room for improvement in the brazeability of the ferritic stainless steels disclosed in Patent Documents 1 and 2. The ferritic stainless steels disclosed in Patent Documents 1 and 2 are both suitable for brazing performed at 1000 to 1200°C, but there was a problem that sufficient brazeability could not be obtained, particularly when brazing at 600 to 950°C using copper phosphorus brazing filler metal.

[0012] The present invention has been developed in view of the above circumstances, and an object of the present invention is to provide a ferritic stainless steel for copper phosphorus brazing that exhibits good brazing properties when brazing is performed using a copper phosphorus brazing material.

[0013] In this case, good brazeability means that when the copper phosphorus brazing material is placed on the surface of the stainless steel sample, the spreadability of the copper phosphorus brazing material is 150% or more when the copper phosphorus brazing material is heated. The spreadability of the copper phosphorus brazing material is calculated by the following formula. Spreadability of phosphorus copper brazing filler metal (%) = [circle equivalent diameter of phosphorus copper brazing filler metal on the surface of the test material after heating (mm)] ÷ [circle equivalent diameter of phosphorus copper brazing filler metal on the surface of the test material before heating (mm)] × 100 Regarding the heating conditions of the phosphorus copper brazing material, etc., please refer to the description of the examples described later. [Means for solving the problem]

[0014] Brazing is a technique for joining base materials by melting a brazing filler metal and utilizing the metallic bond that occurs between the brazing filler metal and the base material. However, an oxide film is formed on the surface of the base material during brazing heat treatment, which inhibits the formation of a metallic bond between the brazing filler metal and the base material and the wetting of the brazing filler metal. For this reason, in order to improve brazing performance, it is necessary to prevent the formation of the oxide film. As a method for this, it has been considered to suppress the formation of the oxide film by reducing the elements contained in stainless steel that are particularly prone to forming an oxide film (hereinafter also referred to as easily oxidizable elements).

[0015] However, when brazing is performed using a copper phosphorus brazing filler metal, sufficient brazeability cannot be obtained simply by reducing the amount of easily oxidizable elements.

[0016] Therefore, the present inventors have conducted extensive research into a method for suppressing the formation of an oxide film on the surface layer of a base material and ensuring good brazing properties when brazing is performed using a phosphorus copper brazing filler metal.

[0017] As a result, they discovered that by strictly controlling the content of easily oxidizable elements and adding a certain amount of Cu, it is possible to suppress the formation of an oxide film and obtain good brazing properties.

[0018] The present inventors consider the mechanism by which the inclusion of Cu suppresses the formation of an oxide film as follows. Cu concentrates on the surface layer of the base material during brazing. The concentration of Cu on the surface layer of the base material reduces the diffusion of easily oxidized elements to the surface layer of the base material, suppressing the formation of an oxide film of these elements (easily oxidized elements). On the other hand, the oxidation of Cu progresses at the same time as the concentration of Cu, and Cu oxide is formed. However, since Cu oxide has a high affinity with phosphorus copper brazing filler metal, Cu oxide does not hinder phosphorus copper brazing. Therefore, by including an appropriate amount of Cu, it is possible to suppress the formation of an oxide film that hinders brazing, and to obtain good brazing performance.

[0019] The present invention was completed based on the above findings and after further investigation.

[0020] That is, the gist and configuration of the present invention are as follows. [1] In mass percent, C: 0.003 to 0.020%, Si: 0.01 to 0.60%, Mn: 0.01 to 0.40%, P: 0.040% or less, S: 0.020% or less, Cr: 16.0-27.0%, Ni: 0.01 to 2.50%, Al: 0.010% or less, Cu: 0.40-0.80%, Nb: 0.10-0.50%, N: 0.020% or less The remainder of the composition of the ferritic stainless steel for copper phosphorus brazing is Fe and unavoidable impurities. [2]Further, in mass percent: Mo: 0.01 to 2.50%, Co: 0.01 to 0.70%, W: 0.01 to 1.00%, The ferritic stainless steel for copper phosphorus brazing according to [1] contains one or more selected from the following: [3] Furthermore, in mass percent: Ti: 0.01 to 0.10%, V: 0.01 to 0.20%, Zr: 0.01 to 0.10%, Mg: 0.0005~0.0050%, Ca: 0.0005 to 0.0050%, B: 0.0005~0.0050%, REM (rare earth metal): 0.001~0.100%, Sn: 0.001 to 0.300%, Sb: 0.001 to 0.100%, The ferritic stainless steel for copper phosphorus brazing according to [1] or [2] contains one or more selected from the following: [4] A water heater assembled using the ferritic stainless steel for copper phosphorus brazing according to any one of [1] to [3] above, with at least one joint being brazed using a copper phosphorus brazing material. Effect of the Invention

[0021] According to the present invention, it is possible to provide a ferritic stainless steel for copper phosphorus brazing that exhibits good brazing properties when brazing is performed using a copper phosphorus brazing material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The present invention will be specifically described below.

[0023] First, the reason why the composition of the steel is limited to the above range in the present invention will be explained. Note that the unit of the content of elements in the composition of the steel is "mass%", but hereinafter, it will be simply expressed as "%" unless otherwise specified.

[0024] C: 0.003 to 0.020% A high C content improves strength, while a low C content improves workability. Here, the C content must be 0.003% or more to obtain sufficient strength. However, if the C content exceeds 0.020%, the workability is significantly reduced, and Cr carbides are precipitated at the grain boundaries, causing sensitization and making the corrosion resistance more likely to decrease. Therefore, the C content is set to a range of 0.003 to 0.020%. The C content is preferably 0.004% or more. The C content is preferably 0.015% or less, and more preferably 0.010% or less.

[0025] Silicon: 0.01 to 0.60% Silicon is a useful element as a deoxidizer, and its effect can be obtained with a silicon content of 0.01% or more. However, if the silicon content exceeds 0.60%, silicon-enriched substances such as silicon oxides and silicon nitrides are generated on the steel sheet surface during brazing heat treatment, and brazing properties are reduced. Therefore, the silicon content is set to a range of 0.01 to 0.60%. The silicon content is preferably 0.10% or more. The silicon content is preferably 0.55% or less, and more preferably 0.50% or less.

[0026] Mn: 0.01 to 0.40% Mn has a deoxidizing effect, and this effect can be obtained with a Mn content of 0.01% or more. However, if the Mn content exceeds 0.40%, Mn concentrates are generated on the steel sheet surface during brazing heat treatment, and brazeability is reduced. Therefore, the Mn content is set to a range of 0.01 to 0.40%. The Mn content is preferably 0.10% or more, and more preferably 0.15% or more. Moreover, the Mn content is preferably 0.25% or less, and more preferably 0.20% or less.

[0027] P:0.040% or less P is an element that is inevitably contained in steel, and excessive content reduces weldability and makes intergranular corrosion more likely to occur. This tendency becomes more pronounced when the P content exceeds 0.040%. Therefore, the P content is set to 0.040% or less. Preferably, the P content is 0.030% or less. There is no particular lower limit for the P content. However, since excessive de-P leads to increased costs, the P content is preferably 0.010% or more.

[0028] S: 0.020% or less S is an element that is inevitably contained in steel, and an S content of more than 0.020% promotes the precipitation of MnS and reduces corrosion resistance. Therefore, the S content is set to 0.020% or less. The S content is preferably 0.010% or less. The lower limit of the S content is not particularly limited. However, since excessive de-S leads to an increase in costs, the S content is preferably 0.0005% or more.

[0029] Cr: 16.0~27.0% Cr is effective in ensuring corrosion resistance. If the Cr content is less than 16.0%, sufficient corrosion resistance cannot be obtained after brazing. However, if the Cr content exceeds 27.0%, a Cr oxide film is formed on the steel sheet surface during brazing, deteriorating the brazeability. Therefore, the Cr content is set to a range of 16.0 to 27.0%. The Cr content is preferably 18.0% or more, and more preferably 19.0% or more. In addition, the Cr content is preferably 23.0% or less, and more preferably less than 22.5%.

[0030] Ni: 0.01 to 2.50% Ni is effective in ensuring corrosion resistance and toughness, and this effect is obtained when the content is 0.01% or more. On the other hand, if the Ni content exceeds 2.50%, the workability decreases. Therefore, the Ni content is set to 0.01 to 2.50%. The Ni content is preferably 0.05% or more, and more preferably 0.10% or more. In addition, the Ni content is preferably 0.60% or less, and more preferably 0.40% or less.

[0031] Al: 0.010% or less Al is a useful element for deoxidation. However, if the Al content exceeds 0.010%, Al-enriched substances such as Al oxides and Al nitrides are likely to be formed on the steel sheet surface during brazing heat treatment, resulting in a decrease in brazability. Therefore, the Al content is set to 0.010% or less. The Al content is preferably 0.005% or less. The lower limit of the Al content is not particularly limited. However, in order to obtain the deoxidation effect by adding Al, the Al content is preferably 0.001% or more.

[0032] Cu: 0.40-0.80% Cu is one of the important elements in the present invention. As described above, by properly adjusting the composition and then containing an appropriate amount of Cu, the generation of an oxide film caused by other easily oxidizable elements is suppressed, and brazing properties using a phosphorus copper brazing material are improved. In order to obtain such effects, the Cu content is set to 0.40% or more. However, if the Cu content exceeds 0.80%, the hot workability and corrosion resistance are reduced. Therefore, when Cu is contained, the Cu content is set to a range of 0.40 to 0.80%. The Cu content is preferably 0.70% or less, more preferably 0.60% or less.

[0033] Nb: 0.10-0.50% Nb is an element that inhibits the decrease in corrosion resistance (sensitization) caused by the precipitation of Cr carbonitrides by combining with C and N. These effects are obtained when the Nb content is 0.10% or more. On the other hand, when the Nb content exceeds 0.50%, the hot workability decreases and manufacturability becomes difficult. Therefore, the Nb content is set in the range of 0.10 to 0.50%. The Nb content is preferably 0.30% or more.

[0034] N: 0.020% or less If the N content exceeds 0.020%, the corrosion resistance and workability are significantly reduced. Therefore, the N content is set to 0.020% or less. Preferably, the N content is set to 0.015% or less. More preferably, the N content is set to 0.010% or less. Although there is no particular restriction on the lower limit of the N content, since excessive denitrification leads to an increase in costs, the N content is preferably set to 0.005% or more.

[0035] The basic components of the ferritic stainless steel of the present invention have been described above. In the composition of the present invention, the components other than those described above are Fe and unavoidable impurities.

[0036] The ferritic stainless steel of the present invention may further contain one or more elements selected from Mo, Co and W, each within the range below.

[0037] Mo: 0.01 to 2.50% Mo stabilizes the passivation film of stainless steel to improve corrosion resistance. This effect is obtained when the Mo content is 0.01% or more. However, if the Mo content exceeds 2.50%, surface defects are likely to occur during hot rolling. Therefore, when Mo is contained, the Mo content is set to the range of 0.01 to 2.50%.

[0038] Co: 0.01 to 0.70% Co is an element that enhances corrosion resistance. This effect is obtained when the Co content is 0.01% or more. However, when the Co content exceeds 0.70%, the workability decreases. Therefore, when Co is contained, the Co content is set to a range of 0.01 to 0.70%. When Co is contained, the Co content is more preferably 0.05% or more. Furthermore, when Co is contained, the Co content is more preferably 0.10% or less.

[0039] W: 0.01 to 1.00% W is an element that enhances corrosion resistance. This effect is obtained when the W content is 0.01% or more. However, when the W content exceeds 1.00%, the workability decreases. Therefore, when W is contained, the W content is set to a range of 0.01 to 1.00%. When W is contained, the W content is more preferably 0.50% or less.

[0040] The ferritic stainless steel of the present invention may further contain one or more elements selected from Ti, V, Zr, Mg, Ca, B, REM, Sn, and Sb within the following ranges, respectively.

[0041] Ti: 0.01 to 0.10% Ti bonds with C and N contained in steel and has the effect of preventing sensitization. This effect is obtained with a Ti content of 0.01% or more. On the other hand, Ti is an element active against oxygen, and a Ti content of more than 0.10% generates a Ti oxide film on the steel surface during brazing treatment, reducing brazeability. Therefore, when Ti is contained, the Ti content is set to a range of 0.01 to 0.10%. When Ti is contained, the Ti content is preferably 0.05% or less.

[0042] V: 0.01 to 0.20% Like Ti, V bonds with C and N contained in the steel to prevent sensitization. These effects are obtained when the V content is 0.01% or more. On the other hand, when the V content exceeds 0.20%, the workability decreases. Therefore, when V is contained, the V content is set to a range of 0.01 to 0.20%. When V is contained, the V content is more preferably 0.10% or less.

[0043] Zr: 0.01 to 0.10% Like Ti and Nb, Zr is an element that combines with C and N contained in steel to suppress sensitization. This effect is obtained when the Zr content is 0.01% or more. On the other hand, if the Zr content exceeds 0.10%, the workability decreases. Therefore, when Zr is contained, the Zr content is set to a range of 0.01 to 0.10%. When Zr is contained, the Zr content is more preferably 0.03% or more. Moreover, the Zr content is more preferably 0.05% or less.

[0044] Mg: 0.0005~0.0050% Mg acts as a deoxidizer. This effect is obtained when the Mg content is 0.0005% or more. However, if the Mg content exceeds 0.0050%, the toughness of the steel decreases, and manufacturability decreases. Therefore, when Mg is contained, the Mg content is set to a range of 0.0005% to 0.0050%. When Mg is contained, the Mg content is more preferably 0.0020% or less.

[0045] Ca: 0.0005~0.0050% Ca improves the penetration of the welded portion and improves the weldability. This effect is obtained when the Ca content is 0.0005% or more. However, when the Ca content exceeds 0.0050%, Ca combines with S to generate CaS, which reduces the corrosion resistance. Therefore, when Ca is contained, the Ca content is set to a range of 0.0005 to 0.0050%. When Ca is contained, the Ca content is more preferably 0.0010% or more. Furthermore, when Ca is contained, the Ca content is more preferably 0.0020% or less.

[0046] B: 0.0005~0.0050% B is an element that improves secondary work embrittlement. This effect is manifested when the B content is 0.0005% or more. However, when the B content exceeds 0.0050%, ductility decreases due to solid solution strengthening. Therefore, when B is contained, the B content is set to a range of 0.0005 to 0.0050%. Moreover, when B is contained, the B content is more preferably 0.0020% or less.

[0047] REM (rare earth metal): 0.001~0.100% REM (rare earth metals: elements with atomic numbers 57 to 71, such as La, Ce, and Nb) are effective elements for deoxidization. The effect can be obtained when the REM content is 0.001% or more. However, when the REM content exceeds 0.100%, the hot workability decreases. Therefore, when REM is contained, the REM content is set to the range of 0.001 to 0.100%. When REM is contained, the REM content is more preferably 0.010% or more. Moreover, when REM is contained, the REM content is more preferably 0.050% or less. Note that REM is a collective term for 15 elements, including Sc, Y, and lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71, and the REM content here is the total content of these elements.

[0048] Sn: 0.001 to 0.300% Sn is an element effective in suppressing roughness of the surface during processing. This effect is obtained when the Sn content is 0.001% or more. However, when the Sn content exceeds 0.300%, the hot workability is reduced. Therefore, when Sn is contained, the Sn content is set to a range of 0.001 to 0.300%. When Sn is contained, the Sn content is more preferably 0.050% or less.

[0049] Sb: 0.001 to 0.100% Sb, like Sn, is an element that is effective in suppressing roughness of the surface during machining. This effect is obtained when the Sb content is 0.001% or more. However, when the Sb content exceeds 0.100%, the workability decreases. Therefore, when Sb is contained, the Sb content is set to a range of 0.001 to 0.100%. When Sb is contained, the Sb content is more preferably 0.050% or less.

[0050] In addition, when the content of Mo, Co, W, Ti, V, Zr, Mg, Ca, B, REM, Sn, or Sb described above as the optional components is less than the lower limit value, the component is considered to be included as an unavoidable impurity.

[0051] The term "ferritic" means a structure mainly composed of ferrite phase, specifically, a structure consisting of ferrite phase that accounts for 80% or more, preferably 90% or more, more preferably 95% or more of the area of ​​the entire structure, and a remaining structure (other than the ferrite phase). Examples of the remaining structure include martensite phase and retained austenite phase. It may be a single ferrite phase (the area ratio of the ferrite phase to the entire structure is 100%).

[0052] Here, the area ratio of the ferrite phase is measured as follows. That is, a test piece for cross-sectional observation is prepared from the stainless steel as the test material. Next, the test piece is etched with aqua regia, and then observed with an optical microscope at a magnification of 200 times in 10 fields of view, and the martensite phase, ferrite phase, and retained austenite phase are distinguished from each other based on the structure shape and etching intensity. After that, the area ratio of the ferrite phase is determined for each field of view by image processing, and the arithmetic average value for the 10 fields of view is calculated.

[0053] The shape of the ferritic stainless steel according to one embodiment of the present invention is not particularly limited, but examples include a plate shape (steel plate), a tube shape (steel pipe), and a rod shape (round bar material, square bar, etc.). The thickness (outer diameter in the case of a round bar material) is preferably 0.1 to 15.0 mm.

[0054] Next, a preferred method for producing ferritic stainless steel according to one embodiment of the present invention will be described taking as an example the case of producing a plate-shaped ferritic stainless steel (ferritic stainless steel plate).

[0055] First, a steel material (steel slab) having the above-mentioned composition is hot-rolled to obtain a hot-rolled steel sheet of a predetermined thickness. Then, the hot-rolled steel sheet is optionally subjected to hot-rolled sheet annealing to obtain a hot-rolled annealed steel sheet. Then, the hot-rolled steel sheet or the hot-rolled annealed steel sheet is cold-rolled to obtain a cold-rolled steel sheet of a predetermined thickness. Then, the cold-rolled steel sheet is subjected to cold-rolled sheet annealing to obtain a cold-rolled annealed steel sheet. In this way, a plate-shaped ferritic stainless steel (ferritic stainless steel sheet) having the above-mentioned composition can be manufactured. The conditions of hot rolling, cold rolling, hot-rolled sheet annealing, cold-rolled sheet annealing, etc. are not particularly limited, and may be in accordance with a conventional method.

[0056] For example, in the steelmaking process for producing steel, it is preferable to perform secondary refining of steel melted in a converter or electric furnace by the VOD method or the like to produce steel having the above-mentioned composition. The produced molten steel can be made into a steel material by a known method, but it is preferable to use a continuous casting method in terms of productivity and quality. Next, the steel material is heated to preferably 1050 to 1250°C, and hot-rolled into a hot-rolled steel sheet of a predetermined thickness by hot rolling. Next, the above-mentioned hot-rolled steel sheet is optionally subjected to continuous annealing at a temperature of 900 to 1150°C, and then optionally descaled by pickling or the like to produce a hot-rolled annealed steel sheet. Furthermore, optionally, scale may be removed by shot blasting before pickling.

[0057] The hot-rolled steel sheet or hot-rolled annealed steel sheet may be subjected to cold rolling. The number of cold rolling may be one, but may be two or more with intermediate annealing in between from the viewpoint of productivity and required quality. The total rolling reduction in cold rolling is preferably 60% or more, more preferably 70% or more. Next, the cold-rolled steel sheet obtained by cold rolling is optionally subjected to continuous annealing (finish annealing) at a temperature of preferably 900 to 1150°C, more preferably 950 to 1150°C, and then optionally pickled to obtain a cold-rolled annealed steel sheet. Note that the continuous annealing may be performed by bright annealing, and pickling may be omitted. Furthermore, depending on the application, after the finish annealing, skin pass rolling or the like may be performed to adjust the shape, surface roughness, and material properties of the steel sheet.

[0058] In the above example, the manufacturing method for forming a plate shape was described as an example, but hot working and cold working can also be performed in addition to forming a plate shape. In this case, the conditions for hot working and cold working are not particularly limited, and may be in accordance with a conventional method.

[0059] The ferritic stainless steel according to one embodiment of the present invention is particularly suitable for use as a base material for copper phosphorus brazing. Copper phosphorus brazing is performed, for example, in a vacuum furnace or an atmospheric furnace at a vacuum degree of 4.0×10 -3Brazing is preferably performed in a vacuum atmosphere or a nitrogen carrier atmosphere of 60 Pa to 60 Pa or less. The temperature during brazing is not particularly limited, but is preferably 600 to 950°C. The phosphorus copper brazing material is a Cu alloy for brazing that contains 50 mass% or more of Cu and 4 to 8 mass% of P, and has a melting point adjusted by adding other elements. The shape of the phosphorus copper brazing material is not particularly limited, but is preferably, for example, a paste-like brazing material (a powder brazing material mixed with a binder composed of an organic substance).

[0060] When the ferritic stainless steel of the present invention described above is brazed using a copper-phosphorus brazing filler metal, the Cu contained in the steel acts to suppress the formation of an oxide film caused by other easily oxidizable elements, thereby improving the wettability of the brazing filler metal.

[0061] The ferritic stainless steel of the present invention described above is suitable for use in water heaters such as electric water heaters and latent heat recovery water heaters, in which at least one joint is assembled by brazing using a phosphorus copper brazing material. EXAMPLES

[0062] Steel having the composition shown in Table 1 was melted in a vacuum melting furnace, heated at 1100 to 1200°C for 1 hour, and then hot-rolled to produce a hot-rolled sheet having a thickness of 4.0 mm. After hot-rolled sheet annealing at 950 to 1100°C, the scale was removed by mechanical grinding, and the sheet was cold-rolled to a thickness of 1.0 mm. The surface of the cold-rolled annealed sheet obtained by finish annealing at 950 to 1100°C was polished with emery paper up to No. 800 and degreased with acetone. The cold-rolled and annealed sheets thus treated were brazed with a copper phosphorus brazing filler metal as described below, and the brazeability was evaluated.

[0063] (Evaluation of brazing ability) A test piece 50 mm wide and 50 mm long was cut out from the cold-rolled annealed sheet subjected to the above treatment, and 0.1 g of phosphorus copper brazing material (BCuP-2 (JIS Z 3264:1998), Cu-7.2 mass% P) was placed in a circle of 5 mm diameter on the surface. The test piece was placed horizontally in a vacuum furnace, and after evacuation, nitrogen gas was introduced and heated at 830°C for 10 minutes in a nitrogen atmosphere of 40 Pa. After cooling to room temperature, the circle equivalent diameter of the phosphorus copper brazing material on the surface of the test piece was measured, and the spreading ratio of the phosphorus copper brazing material was calculated according to the following formula. Spreadability of phosphorus copper brazing filler metal (%) = [circle equivalent diameter of phosphorus copper brazing filler metal on the surface of the test piece after heating (mm)] / [circle equivalent diameter of phosphorus copper brazing filler metal on the surface of the test piece before heating (mm)] × 100 Based on the spreadability of the obtained copper phosphorus brazing filler metal, the brazeability of each steel sheet was evaluated as follows. ◎ (Pass, particularly excellent): 250% or more 〇 (Pass): 150% or more but less than 250% × (Fail): Less than 150%

[0064] [Table 1]

[0065] As can be seen from Table 1, all of the inventive examples had good brazeability when using a copper phosphorus brazing filler metal. In particular, inventive examples Nos. 1-2, 6-11, and 13, the contents of easily oxidized elements (Cr and Al) were appropriately regulated, and the Cu content was appropriate, so excellent brazeability was obtained. In contrast, in comparative examples Nos. 14-18, whose composition was outside the appropriate range, good brazeability was not obtained.

[0066] More specifically, in Comparative Example No. 14, the Si content exceeded the upper limit of the present invention, and therefore good brazeability was not obtained. In addition, in Comparative Example No. 15, the Mn content exceeded the upper limit of the present invention, and therefore good brazeability was not obtained. In addition, in Comparative Example No. 16, the Cr content exceeded the upper limit of the present invention, and therefore good brazeability was not obtained. In addition, in Comparative Example No. 17, the Al content exceeded the upper limit of the present invention, and therefore good brazeability was not obtained. In addition, in Comparative Example No. 18, the Cu content was below the lower limit of the present invention, and therefore good brazeability was not obtained. [Industrial Applicability]

[0067] The ferritic stainless steel of the present invention exhibits good brazeability when brazed with a copper phosphorus brazing filler metal, and is therefore particularly suitable for use in water heaters such as electric water heaters and latent heat recovery water heaters, in which at least one joint is assembled by brazing with a copper phosphorus brazing filler metal.

Claims

1. In mass percent, C: 0.003-0.020%, Si: 0.01 to 0.50%, Mn: 0.01 to 0.20%, P: 0.040% or less, S: 0.020% or less, Cr: 16.0-23.0%, Ni: 0.01 to 2.50%, Al: 0.001% or more and 0.005% or less, Cu: 0.40-0.70%, Nb: 0.10 to 0.50%, N: 0.020% or less The remainder of the composition of the ferritic stainless steel for copper phosphorus brazing is Fe and unavoidable impurities.

2. Further, in mass%, Mo: 0.01-2.50%, Co: 0.01 to 0.70%, W: 0.01-1.00%, 2. The ferritic stainless steel for copper phosphorus brazing according to claim 1, which contains one or more selected from the following:

3. Further, in mass%, Ti: 0.01 to 0.10%, V: 0.01-0.20%, Zr: 0.01 to 0.10%, Mg: 0.0005-0.0050%, Ca: 0.0005-0.0050%, B: 0.0005-0.0050%, REM (rare earth metal): 0.001-0.100%, Sn: 0.001-0.300%, Sb: 0.001 to 0.100%, 3. The ferritic stainless steel for copper phosphorus brazing according to claim 1, which contains one or more selected from the following:

4. A water heater using the ferritic stainless steel for copper phosphorus brazing according to any one of claims 1 to 3, wherein at least one joint is assembled by brazing using a copper phosphorus brazing material.

Citation Information

Patent Citations

  • Ferritic stainless steel with good high-temperature strength and preparation method thereof

    CN111057947A

  • Cu-PLATED FERRITIC STAINLESS STEEL SHEET AND MULTIPLY-WOUND STEEL PIPE

    JP2010095768A

  • Stainless steel refrigerant piping for heat exchanger

    JP2011202838A

  • Ferritic stainless steel for tube

    JP2017061748A

  • FERRITIC STAINLESS STEEL EXCELLENT IN Cu BRAZABILITY

    JP2018145497A